Analisis Sentimen Pengguna Sistem E-Kinerja Desa Kabupaten Jembrana Menggunakan Metode Naive Bayes - aditya, eka; Astawa, I Gede Karya; Limbong, Kevin Gary; Indrawan, Gede; Gunawan, Made Agus Oka (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The current era of globalization where information is needed very quickly. However, this is an obstacle, especially at the village level where the performance of the village, especially in rural areas, is difficult to obtain information, because it still uses manual bookkeeping. In response to this, the Jembarana Regency Government has improved its services using the website-based E-Kinerja application. Even though E-Kinerja has been used, it is important to know how user sentiment is when using the E-Kinerja system so that it can be used as an evaluation. This study aims to determine the sentiment of E-Kinerja users using the Naive Bayes method, Naive Bayes is a simple method and has high effectiveness in classification. The results of sentiment analysis with the Naive Bayes method get an accuracy of 66% precison 67% and recall 67% with a total of 88 datasets, an accuracy of 77% precison 69% and recall 69% in a total of 150 datasets.